The Role and Molecular Mechanism of Long Nocoding RNA-MEG3 in the Pathogenesis of Preeclampsia. (December 2018) - Yu, Lin; Kuang, Li-Yun; He, Fang; Du, Li-Li; Li, Qiu-Lian; Sun, Wen; Zhou, Yan-Mei; Li, Xiao-Mei; Li, Xiu-Ying; Chen, Dun-Jin
A growing body of evidence suggests that the dysregulation of long noncoding RNA is increasingly linked to many human diseases. Maternally expressed gene 3 ( MEG3 ) is one such gene thought to be affected. In the placenta of patients with preeclampsia, there is reduced expression of MEG3 ; however, its role and the mechanism involved are not clear. Therefore, we examined the expression of MEG3, epithelial–mesenchymal transition (EMT) markers (E-cadherin and N-cadherin), and TGF-β/smad signaling pathway genes ( TGF-β1, smad3, and smad7 ) in the placental tissues of 20 patients with preeclampsia and 20 healthy patients. We further observed the impact of MEG3 on the invasion and migration functions of human trophoblast cells and the effects on EMT and TGF-β/smad signaling pathways in an Human trophoblast cell-8 (HTR-8)Vneo cell line. The expression of MEG3 was lower in tissues from patients with preeclampsia having an EMT decline, as well as a messenger RNA expression of smad7 . The expression of TGF-β1 and smad3 were higher in patients with preeclampsia. In HTR-8/SVneo cells with overexpressed MEG3, the invasion and migration functions were enhanced and accompanied by higher EMT and a significantly increased expression of smad7 . Our data indicate that MEG3 is closely associated with the pathogenesis of preeclampsia and thus associated with changes in the EMT of placental trophoblast cells. These results indicate that MEG3 regulation of trophoblast cell EMT via the TGF-β pathway inhibitor smad7 may be the molecular mechanism involved in the pathogenesis of preeclampsia.